Acceptance of 3D Printing by Occupational Therapists: An Exploratory Survey Study - Karin Slegers; Anna M. Krieg; Monique A. S. Lexis (Occupational Therapy International, 2022)
Do-it-yourself (DiY) assistive technology gained attention in accessibility literature recently, especially in relation to the rise of digital fabrication technologies, such as 3D printing. Previously, small-scale studies showed that care professionals generally respond positively towards the idea of creating DiY assistive devices for their clients. However, several barriers and concerns may hinder care professionals’ actual adoption of digital fabrication technologies. To better understand occupational therapists’ willingness to adopt 3D printing, we have conducted an exploratory survey study (N=119) based on the unified theory of acceptance and use of technology (UTAUT). Confirming previous studies, occupational therapists in this study showed generally positive attitudes towards adopting 3D printing technology. Factors that may affect their intentions to use 3D printing technology include expectations regarding job performance, effort, social influence, and facilitating conditions, as well as one’s tendency to adopt novel technologies. Furthermore, occupational therapists will likely experience difficulties when first using 3D printing technology, despite their overall positive expectations of the ease of use. Therefore, we recommend that further research should focus on training, but especially on effective ways to support occupational therapists on the job, for instance, by facilitating collaborations with 3D printing experts.